A Digital Twin for the Monastery of Sant Genís de Rocafort, Martorell, Barcelona: Experiences in Research and Dissemination - Isidre Ot Padilla; Esther Travé Allepuz; Pablo Del Fresno Bernal; Josep Socorregut Domènech (Journal of Digital Media & Interaction)
The Monastery of Sant Genís de Rocafort (Martorell, Barcelona) has been the subject of archaeological excavation for over a decade. This work has uncovered Romanesque structures and some earlier elements, significantly enhancing our understanding of this monument, which is listed as a BCIN (Cultural Asset of National Interest), and its history. However, the site’s location and accessibility challenges have limited the opportunity for certain audiences to visit and learn about it. In this context, the research team has developed a digital twin of the monastery, a three-dimensional recreation that offers significant potential both for heritage dissemination and basic archaeological research. This project has enabled precise documentation of the structures and created an accessible resource that brings the monastery to a wide range of audiences while also allowing us to experiment with different reconstruction hypotheses. The process of creating the digital twin has raised a series of methodological and conceptual challenges, such as the selection of technological tools and decisions about how to present the site’s narrative. This article reflects on the experience gained throughout this process, exploring the implications of these decisions for both archaeological research and cultural dissemination.